2014
DOI: 10.1039/c3ra44493g
|View full text |Cite
|
Sign up to set email alerts
|

Safe and facile hydrogenation of commercial Degussa P25 at room temperature with enhanced photocatalytic activity

Abstract: In this paper, we developed a new safe and facile route to prepare black titania at room temperature for visible light photocatalysis. The commercial Degussa P25 was used as the starting material, and it was hydrogenated at 35 bar hydrogen and room temperature for up to 20 days. The resulting hydrogenated P25 was characterized by XRD, FT-IR, Raman, UV-Vis, TEM and photocatalysis tests under visible light in methanol solution. It was found that P25 powders under hydrogen treated for more than 15 days have a dar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(99 citation statements)
references
References 25 publications
5
94
0
Order By: Relevance
“…Color change from white to black for TiO 2 nanomaterials reflects the change in optical properties and thus suggests the structural change after modification, at least the surface structural change. High-resolution transmission electron microscope (HRTEM) has revealed that a number of black TiO 2 nanomaterials have a crystalline/ amorphous core/shell structure, while white ones have clear lattice fringes throughout the crystals [22,23,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. The amorphous or disordered surface layer has been considered the typical feature of black TiO 2 nanomaterials.…”
Section: Basic Properties Of Black Tio 2 Versusmentioning
confidence: 99%
“…Color change from white to black for TiO 2 nanomaterials reflects the change in optical properties and thus suggests the structural change after modification, at least the surface structural change. High-resolution transmission electron microscope (HRTEM) has revealed that a number of black TiO 2 nanomaterials have a crystalline/ amorphous core/shell structure, while white ones have clear lattice fringes throughout the crystals [22,23,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. The amorphous or disordered surface layer has been considered the typical feature of black TiO 2 nanomaterials.…”
Section: Basic Properties Of Black Tio 2 Versusmentioning
confidence: 99%
“…In the hydrogenation method, the surface of TiO 2 is terminated with hydrogen leading to an enhanced photocatalytic activity35 in visible region; however, it is still unknown that how does the hydrogenation modify a surface to enhance its optical performance (photocatalytic activity)36. The drawback of the hydrogenation method is that it requires high temperature and the obtained TiO 2 sample/film are black35, which makes the films unable for many optoelectronic applications, such as a transparent electrode in optoelectronic devices. Both the vacuum activation and plasma treatment methods create highly stable Ti 3+ and oxygen vacancies3234.…”
mentioning
confidence: 99%
“…[15,16] However, a large interest on the hydrogeantion of TiO 2 nanomaterials did not appear until our report of the striking color change into black color and the related dramatic electronic and photocatalytic property changes. [17][18][19][20][21][22][23][24][25] When anatase TiO 2 nanocrystals go through hydrogenation under Functional Oxides Prospective Article high-pressure H 2 environment at 200°C for a few days, a crystalline/disordered core/shell nanoparticle is formed without detectable species of reduced Ti 3+ ions using both surface and bulk chemical measurement techniques (such as x-ray photoelectron spectrosocpy and x-ray absorption spectroscopy), surprising contradictory to our common sense that reduced form of Ti 4+ ions would form under such condition. [4,[18][19][20] The hydrogen employed is found to play an important role in stabilizing the disordered layer, which makes a large contribution to the long-wavelength absorption and the enhanced charge separation and photocatalytic activity.…”
Section: Hydrogenated Tio 2 Nanomaterialsmentioning
confidence: 99%
“…[4] Since the striking discovery of the hydrogenated black TiO 2 nanoparticles, extensive researches have been conducted to enrich our understanding in the preparation and properties of various hydrogenated TiO 2 nanomaterials. Not surprisingly, it has been found that the extents of the color and optical spectrum changes, the formation of the crystalline/disordered core/shell nanostructures, [4,[21][22][23][24][25][26] the existence of possible Ti…”
Section: Hydrogenated Tio 2 Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation